Christianity, Social Justice, and the Japanese American Incarceration during World War II - Blankenship, Anne M. (Book collections on Project MUSE., 2016)
This study of Christianity in the infamous camps where Japanese Americans were incarcerated during World War II yields insights both far-reaching and timely. Anne Blankenship shows how church leaders were forced to assess the ethics and pragmatism of fighting against or acquiescing to what they clearly perceived, even in the midst of a national crisis, as an unjust social system.